Introduction. In Search of Economic Policies to Stabilise Democratic Transitions - Giacomo Luciani (Revue Internationale de Politique de Développement)
Democratic transitions in the Middle East and North Africa have mostly failed to consolidate and have been hindered by the difficult economic heritage of previous authoritarian governments. Yet newly established democratic governments must deliver on the expectations of their people, especially the poorer strata, otherwise disillusionment may open the door to restoration of authoritarian rule. The introductory chapter reviews existing literature on the topic and presents the contributions of the collective volume to this crucially important discussion. Can democracy succeed? Various ideas for economic policies that may help consolidate the democratisation process are proposed, while major obstacles on the way to democratic success are also highlighted.